1997
DOI: 10.1159/000134686
|View full text |Cite
|
Sign up to set email alerts
|

A proposed nomenclature of the domestic cat karyotype

Abstract: High-resolution G- and Q-band patterns of cat (Felis catus) prometaphase chromosomes with more than 450 numbered bands are presented. This number represents approximately twice the number of bands per haploid set exhibited by feline chromosomes at mid-metaphase. A diagrammatic representation of G-banded cat chromosomes has already been described (O’Brien and Nash, 1982); however, precise numbering of bands and landmarks, as in the human karyotype and in the karyotypes of other domestic and laboratory animals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2025
2025

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Together, these markers cover all 18 feline autosomes and X and Y chromosomes, with all but two loci occupying unique coordinates on the map. Twohundred ninety-one loci have been ordered at odds Ն1000:1, with an additional 54 loci ordered at odds (Cho et al 1997d) are shown to the left of each map. Hybridization results from human on cat chromosome painting (Rettenberger et al 1995;Wienberg et al 1997) are depicted to the left of each ideogram for comparison to the RH-derived syntenies.…”
Section: Map Construction and Characterizationmentioning
confidence: 99%
“…Together, these markers cover all 18 feline autosomes and X and Y chromosomes, with all but two loci occupying unique coordinates on the map. Twohundred ninety-one loci have been ordered at odds Ն1000:1, with an additional 54 loci ordered at odds (Cho et al 1997d) are shown to the left of each map. Hybridization results from human on cat chromosome painting (Rettenberger et al 1995;Wienberg et al 1997) are depicted to the left of each ideogram for comparison to the RH-derived syntenies.…”
Section: Map Construction and Characterizationmentioning
confidence: 99%
“…The probe was purified using a G50 Sephadex column (Pharmacia) following the manufacturer's instructions and Cho et al (1997b).…”
Section: Mapping Of Type I Markers Onto Dog Chromosomesmentioning
confidence: 99%
“…1b. The application of the CFA 5 paint to cat metaphase chromosome spreads revealed blocks of signal on four chromosome pairs. These regions were identified as FCA C1p22, D1p13→ p12, E1p14 → p13, and E2q13 → q14 on the basis of their DAPI-banding patterns, as compared to the G-banded ideogram of Cho et al (1997b). The data are presented in Fig.…”
Section: Reciprocal Chromosome Paintingmentioning
confidence: 99%
“…The FGFasL clone contained F11-kb insert of feline genomic FasL and was used for FISH. Based on the nomenclature for feline Q-banded chromosomes (Cho et al, 1997), the chromosome locus was determined. (Mizuno et al, 1998) Gene reference: The nucleotide sequence of feline FasL cDNA was published in Mizuno et al (1998).…”
Section: Methodsmentioning
confidence: 99%